Multi-sector Collaboration for Students of different levels to Learn Digital Technology Skills using Competency Assessment from Learning to Create pieces with a 3D printers for Young Innovators Case Study: MogroWittayakom School - Alongkot Terdyothin; Tuanjai Archevapanich; Manit Chansuthirangkool; Pondthip Inyoo; Thanavit Anuwongpinit; Boonchana Purahong (My University, 2024)
This article is the result of collaboration across various associations to create learning spaces for students in compulsory and optional education as well as living skills. This article provides an example of learning digital technology skills through collaboration, starting with the establishment of an innovation room, followed by instructional activities to explore assessment methods for competency in creating works using a 3D printer tailored for young innovators. By employing rubric- based technology tailored to real-world conditions, it aims to fulfill teachers' expectations for student outcomes. This approach helps students understand and apply a rubric to evaluate and improve their own creations. The demographic involves 20 high school students from MogroWittayakhom, selected through purposive sampling. The students participated in a practical performance test, receiving step-by-step training over two days, totaling 12 hours. Upon completing the instruction, students designed and fabricated their projects using Tinkercad software, which were then printed with a 3D printer. The instructor evaluated the students using a rubric-based competency assessment with three scoring levels. The results showed that all 20 participants achieved a high competency level as per the rubric, validating the hypothesis with 100% of the participants meeting the performance criteria.
Keywords: Mobile Learning in Education; Innovative Teaching and Learning Methods; E-Learning and Knowledge Management